Catalyst slurry as well as preparation method and application thereof

By using high-pressure nanodispersion technology in the preparation process of catalyst slurry, the stability problem caused by uneven distribution of catalyst particles is solved, and the performance and stability of the membrane electrode are significantly improved, which is suitable for large-scale production.

CN119838461APending Publication Date: 2025-04-18FTXT ENERGY TECH CO LTD

Patent Information

Application Number
CN202311344023.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art cannot effectively solve the problem of poor stability caused by uneven distribution of fine particles in catalyst slurry, which in turn affects the performance of membrane electrodes.

Method used

The first ionomer solution is first premixed with the catalyst, then added with the first solvent to form a first slurry, followed by the second ionomer solution and the second solvent, and finally perform high-pressure nanodispersion, a catalyst slurry with higher stability is prepared.

Benefits of technology

This method effectively improves the stability of the catalyst slurry, reduces the formation of agglomerates, improves the uniformity of the catalytic layer and the performance of the membrane electrode, and simplifies operations and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides catalyst slurry as well as a preparation method and application thereof. The method comprises the following steps: premixing a first ionomer solution and a catalyst, and adding a first solvent into the system for first mixing to form first slurry; performing second mixing on the first slurry, a second ionomer solution and a second solvent to form second slurry; performing high-pressure nano-dispersion on the second slurry to obtain catalyst slurry; wherein the first ionomer solution is prepared from the following components in percentage by weight: 5 to 30 percent of perfluorinated sulfonic acid resin and 70 to 95 percent of water; the second ionomer solution is prepared from the following components in percentage by weight: 5 to 30 percent of perfluorinated sulfonic acid resin, 10 to 70 percent of alcohol solvent and 0 to 50 percent of water. On the basis, the catalyst slurry is better in stability, and the membrane electrode performance is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of membrane electrode technology, and in particular to a catalyst slurry and a preparation method and application thereof. Background Art

[0002] Catalyst slurry is generally composed of catalyst / carrier, solvent and ionomer. The inventors found that whether the clusters formed by ionomer and catalyst can be evenly distributed in the catalyst layer will affect the formation of apparent cracks in the catalyst layer, as well as the formation of defects such as pores, thereby affecting the three-phase interface reaction of the catalyst layer. Therefore, the rational design of the micromorphology of ionomer in the slurry is an important aspect of improving the performance of fuel cells. In actual application, the stability of the catalyst slurry is an important factor affecting its performance (such as electrochemical performance and durability). Stability is defined as: the stability of the slurry properties (particle size) over time. Fine particles (particles formed by catalyst particles coated with perfluorosulfonic acid resin) are constantly in Brownian motion in the slurry, and particles are constantly colliding. If the collision can overcome the energy barrier, it is easy for particles to aggregate or flocculate, which is extremely unfavorable for the use and storage of the slurry, hindering the large-scale production of fuel cells.

[0003] In order to solve the above-mentioned agglomeration problem of catalyst particles, Chinese Patent 201811175737.1 discloses a method for preparing a fuel cell membrane electrode slurry, which is characterized by adding polyacrylamide, acetic acid and a thickener to the slurry to reduce the agglomeration of catalyst particles and improve the dispersion performance of the catalyst. Chinese Patent 201611063880.2 discloses a method for preparing a fuel cell membrane electrode catalyst slurry, the slurry components include catalyst particles, water, a polymer proton conductor solution, and a Teflon solution, and the agglomeration of catalyst particles is improved by regulating the slurry components, the order of adding materials and the dispersion method.

[0004] However, the above-mentioned prior art solutions cannot effectively solve the problems such as poor stability of the catalyst slurry due to the uneven size distribution of fine particles in the catalyst slurry (particles formed by the catalyst particles coated with perfluorosulfonic acid resin), which in turn leads to poor membrane electrode performance. At the same time, the above-mentioned technical solution also has the problem of complex operation, which is not conducive to large-scale production of slurry, and even introduces some additional substances that will associate with the catalyst slurry (such as sodium alginate, gelatin, polyvinyl pyrrolidone, sodium polyacrylate, etc.), affecting the activity and durability of the membrane electrode. Therefore, it is necessary to provide a new method for preparing catalyst slurry to improve the above problems. Summary of the invention

[0005] The main purpose of the present invention is to provide a catalyst slurry and a preparation method and application thereof, so as to solve the problem that the prior art cannot effectively solve the problem of poor stability of the catalyst slurry due to the uneven size distribution of fine particles (catalyst particles formed by coating with perfluorosulfonic acid resin) in the catalyst slurry, which in turn leads to poor membrane electrode performance.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a catalyst slurry is provided, comprising: firstly pre-mixing a first ionomer solution and a catalyst, and then adding a first solvent into the system for a first mixing to form a first slurry; performing a second mixing of the first slurry, a second ionomer solution and a second solvent to form a second slurry; performing high-pressure nano-dispersion on the second slurry to obtain a catalyst slurry; wherein, in terms of weight percentage, the first ionomer solution comprises 5 to 30 wt% of a perfluorosulfonic acid resin and 70 to 95 wt% of water; and the second ionomer solution comprises 5 to 30 wt% of a perfluorosulfonic acid resin, 10 to 70 wt% of an alcohol solvent and 0 to 50 wt% of water.

[0007] Furthermore, the catalyst is selected from one or more of a platinum-carbon catalyst, a platinum-cobalt alloy-carbon catalyst or a platinum-cobalt-manganese ternary alloy-carbon catalyst.

[0008] Further, the I / C value of the catalyst slurry is 0.4-1.2; preferably, the ratio of the I / C value of the first ionomer solution to the I / C value of the second ionomer solution is 0.25-3:1.

[0009] Further, the ion exchange equivalent value of the first ionomer solution is smaller than the ion exchange equivalent value of the second ionomer solution; preferably, the ion exchange equivalent value of the first ionomer solution is ≤810; preferably, the ion exchange equivalent value of the second ionomer solution is ≤1050.

[0010] Furthermore, the temperature of the first solvent and the second solvent is independently -5 to 10°C; preferably, the first solvent and the second solvent are independently selected from C1-C3 alcohol solvents, and more preferably, the first solvent and the second solvent are independently selected from one or more of n-propanol, isopropanol, ethanol or methanol.

[0011] Furthermore, the stirring rate in the premixing process is 50-200 rpm, and the stirring time is 5-60 min; preferably, the stirring rate in the first mixing process is 100-500 rpm, and the stirring time is 20-40 min; further preferably, the stirring rate in the second mixing process is 50-500 rpm, and the stirring time is 30-180 min.

[0012] Furthermore, the dispersion pressure in the high-pressure nano-dispersion process is 80 to 150 MPa, and the number of nano-dispersion times is 3 to 8 times.

[0013] Furthermore, the solid content of the catalyst slurry is 8-14 wt%.

[0014] In order to achieve the above object, according to one aspect of the present invention, a catalyst slurry prepared by the above preparation method is provided.

[0015] According to another aspect of the present invention, there is provided a use of the aforementioned catalyst slurry in a process for preparing a proton exchange membrane fuel cell.

[0016] The technical solution of the present invention can effectively solve the problem of poor stability of the catalyst slurry caused by uneven size distribution of fine particles in the catalyst slurry (particles formed by catalyst particles coated with perfluorosulfonic acid resin), which in turn leads to poor membrane electrode performance. DETAILED DESCRIPTION

[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0018] As described in the specification of this application, the prior art cannot effectively solve the problem of poor stability of the catalyst slurry due to the uneven size distribution of fine particles (particles formed by the catalyst particles being coated with perfluorosulfonic acid resin) in the catalyst slurry, which in turn leads to poor membrane electrode performance. In order to solve this problem, the present application provides a method for preparing a catalyst slurry, which includes: first pre-mixing a first ionomer solution and a catalyst, then adding a first solvent to the system for a first mixing to form a first slurry; second mixing the first slurry, the second ionomer solution and the second solvent to form a second slurry; high-pressure nano-dispersing the second slurry to obtain a catalyst slurry; wherein, by weight percentage, the first ionomer solution is composed of 5 to 30 wt% of perfluorosulfonic acid resin and 70 to 95 wt% of water; the second ionomer solution is composed of 5 to 30 wt% of perfluorosulfonic acid resin, 10 to 70 wt% of alcohol solvent and 0 to 50 wt% of water.

[0019] The inventors have found that whether the clusters formed by the ionomer and the catalyst can be evenly distributed in the catalyst layer will affect whether there are defects such as cracks and pores on the surface of the catalyst layer, which will in turn affect the three-phase interface reaction of the catalyst layer. Therefore, the reasonable design of the microscopic morphology of the ionomer in the slurry is an important aspect of improving the performance of the fuel cell. Based on this, the present application proposes for the first time that a first ionomer solution (composed of 5 to 30 wt% of perfluorosulfonic acid resin and 70 to 95 wt% of water), a catalyst and a first solvent can be mixed for a first time to form a first slurry; then a second ionomer solution (composed of 5 to 30 wt% of perfluorosulfonic acid resin, 10 to 70 wt% of alcohol solvent and 0 to 50 wt% of water) and a second solvent are added to the first slurry for a second mixing to form a second slurry; the second slurry is subjected to high-pressure nano-dispersion to obtain a catalyst slurry.

[0020] In this way, the first ionomer solution of the water base can pre-coat the catalyst to form a pre-cluster, and then add the second ionomer solution of the alcohol base to carry out the high-pressure nano-dispersion process, and the ionomer is dispersed in the slurry in a more orderly manner, and the agglomerates are more difficult to form, and the size of the agglomerates is smaller, so that it can be more uniformly adsorbed on the catalyst, thereby greatly improving the stability of the catalyst slurry. When subsequently applied in a fuel cell, the clusters formed by the ionomer and the catalyst are evenly distributed in the catalyst layer, and the catalyst layer will not produce defects such as cracks and pores on the surface, and the fuel cell performance is excellent. At the same time, such operation can also effectively avoid the risk of fire caused by the combination of the catalyst and alcohols, and the safety performance is better. And the preparation method is simple, suitable for the large-scale preparation of slurry, and other substances that will associate with the catalyst will not be introduced.

[0021] In order to further improve the stability of the slurry, in a preferred embodiment, the ratio of the I / C value of the first ionomer solution to the I / C value of the second ionomer solution is 0.25 to 3:1, for example, it can be 0.25:1, 0.5:1, 1:1, 2:1. In a preferred embodiment, the I / C value of the first ionomer solution is 0.2 to 0.6, and the I / C value of the second ionomer solution is 0.2 to 0.8. In a preferred embodiment, the I / C value of the catalyst slurry is 0.4 to 1.2, for example, it can be 0.4, 0.8, 1.0, 1.2. It is further explained here that the I / C value refers to: the solid mass of perfluorosulfonic acid resin in the ionomer solution / the carbon mass in the catalyst.

[0022] In order to further improve the stability of the slurry, in a preferred embodiment, the ion exchange equivalent value of the first ionomer solution is less than the ion exchange equivalent value of the second ionomer solution. The ion exchange equivalent value of the first ionomer solution is ≤810, preferably 650-750; the ion exchange equivalent value of the second ionomer solution is ≤1050, preferably 750-850.

[0023] Considering that the addition of solvents (such as alcohols) may cause the slurry temperature to rise, thereby causing the catalyst and ionomer cluster particles to be unstable, it is further preferred that the temperature of the first solvent and the second solvent is independently -5 to 10° C., for example, -5° C., 0° C., 5° C. or 10° C. The first solvent and the second solvent are independently selected from C1-C3 alcohol solvents, and more preferably, the first solvent and the second solvent are independently selected from one or more of n-propanol, isopropanol, ethanol or methanol.

[0024] In some optional embodiments, the catalyst is selected from one or more of a platinum-carbon catalyst, a platinum-cobalt alloy-carbon catalyst, or a platinum-cobalt-manganese ternary alloy-carbon catalyst.

[0025] Considering that a large number of bubbles generated during the mixing process will affect the stability of the slurry, in a preferred embodiment. The stirring rate during the premixing process is 50-200rpm, for example, 50rpm, 100rpm, 150rpm or 200rpm; the stirring time is 5-60min, for example, 5min, 10min, 20min, 30min, 40min, 50min or 60min. The stirring rate during the first mixing process is 100-500rpm, for example, 100rpm, 200rpm, 300rpm, 400rpm or 500rpm; the stirring time is 20-40min, for example, 20min, 30min or 40min. The stirring rate during the second mixing process is 50-500rpm, for example, 50rpm, 100rpm, 200rpm, 300rpm, 400rpm or 500rpm; the stirring time is 30-180min, for example, 30min, 60min, 90min, 120min, 150min or 180min. At this stirring rate, the generation of bubbles can be effectively avoided on the basis of uniform mixing of materials.

[0026] In order to further improve the dispersion effect and obtain a slurry with suitable particle size and better uniformity, the dispersion pressure in the high-pressure nano-dispersion process is preferably 80 to 150 MPa, for example, 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa or 150 MPa, and the number of nano-dispersion is 3 to 8 times.

[0027] In order to further balance the comprehensive properties of the slurry, in a preferred embodiment, the solid content of the catalyst slurry is 8-14%.

[0028] The present application also provides a catalyst slurry prepared by the above-mentioned method for preparing a catalyst slurry. Based on the above reasons, in the catalyst slurry of the present application, the ionomer is dispersed more orderly in the slurry, the agglomerates are more difficult to form, and the size of the agglomerates is smaller, so that they can be more uniformly adsorbed on the catalyst, and the stability of the catalyst slurry is better.

[0029] The present application also provides an application of the aforementioned catalyst slurry in a proton exchange membrane fuel cell. Based on the above reasons, the fuel cell performance is better. The clusters formed by the ionomer and the catalyst are evenly distributed in the catalyst layer, and there are no defects such as cracks and pores on the surface of the catalyst layer, and the fuel cell performance is greatly improved.

[0030] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0031] Example 1

[0032] 4 g of 50% platinum-carbon catalyst (TKK TEC10E50E 50% platinum-carbon catalyst) and 10 g of a first ionomer solution (composed of 10 wt % of perfluorosulfonic acid resin Solvay 1172 and 90 wt % of water, with an ion exchange equivalent value of 720) were mixed and stirred at a magnetic stirrer at 100 rpm for 5 minutes, and then 18 g of 10° C. n-propanol was added. After stirring at a magnetic stirrer at 200 rpm for 30 minutes, 4 g of a second ionomer solution (composed of 25 wt % of perfluorosulfonic acid resin Solvay 32579, 35 wt % of ethanol and 40 wt % of water, with an ion exchange equivalent value of 790) and 18 g of 10° C. n-propanol were added. After stirring at a magnetic stirrer at 400 rpm for 120 minutes, high-pressure nanodispersion was performed, the dispersion pressure was 80 MPa, and the number of nanodispersion times was 5.

[0033] The solid content of the catalyst slurry is 11.1%. The I / C value of the catalyst slurry is 1.0. The I / C ratio of the first ionomer solution and the second ionomer solution is 1:1.

[0034] Example 2

[0035] The only difference from Example 1 is that the dispersion pressure is 120 MPa.

[0036] Example 3

[0037] The only difference from Example 1 is that the dispersion pressure is 150 MPa.

[0038] Example 4

[0039] The only difference from Example 1 is that the dispersion pressure is 180 MPa.

[0040] Example 5

[0041] The only difference from Example 1 is that the amount of the first ionomer solution is 13.3 g, the amount of the second ionomer solution is 2.68 g, and the I / C ratio of the first ionomer solution to the second ionomer solution is 2:1.

[0042] The solid content of the catalyst slurry was 10.72%. The I / C value of the catalyst slurry was 1.0.

[0043] Example 6

[0044] The only difference from Example 1 is that the amount of the first ionomer solution is 16 g, the amount of the second ionomer solution is 1.6 g, and the I / C ratio of the first ionomer solution to the second ionomer solution is 4:1.

[0045] The solid content of the catalyst slurry was 10.42%. The I / C value of the catalyst slurry was 1.0.

[0046] Comparative Example 1

[0047] 4 g of 50% platinum carbon catalyst was weighed, and 20 g of ionomer solution (composed of 10 wt % perfluorosulfonic acid resin and 90 wt % water) with an ion exchange equivalent value of 1000 was added. After stirring with a magnetic stirrer at 400 rpm for 120 minutes, high-pressure nano-dispersion was performed, the dispersion pressure was 80 MPa, and the number of nano-dispersion times was 5.

[0048] Comparative Example 2

[0049] 4 g of 50% platinum carbon catalyst and 10 g of the first ionomer solution (composed of 10 wt % of perfluorosulfonic acid resin and 90 wt % of water, with an ion exchange equivalent value of 720) were mixed and stirred at a magnetic stirrer at 100 rpm for 5 minutes, and then 18 g of 10° C. n-propanol was added. The mixture was stirred at 200 rpm for 30 minutes, and then 10 g of the first ionomer solution (composed of 10 wt % of perfluorosulfonic acid resin and 90 wt % of water, with an ion exchange equivalent value of 720) and 18 g of 10° C. n-propanol were added. The mixture was stirred at 400 rpm for 120 minutes, and then high-pressure nano-dispersion was performed, with a dispersion pressure of 80 MPa and a nano-dispersion frequency of 5 times.

[0050] Comparative Example 3

[0051] 4 g of 50% platinum carbon catalyst and 10 g of a second ionomer solution (composed of 25 wt % of perfluorosulfonic acid resin, 35 wt % of ethanol and 40 wt % of water, with an ion exchange equivalent value of 790) were mixed and stirred at a magnetic stirrer at 100 rpm for 5 minutes, and then 18 g of 10° C. n-propanol was added. The mixture was stirred at 200 rpm for 30 minutes, and then 10 g of the second ionomer solution (composed of 25 wt % of perfluorosulfonic acid resin, 35 wt % of ethanol and 40 wt % of water, with an ion exchange equivalent value of 790) and 18 g of 10° C. n-propanol were added. The mixture was stirred at 400 rpm for 120 minutes, and then high-pressure nano-dispersion was performed, with a dispersion pressure of 80 MPa and a nano-dispersion frequency of 5 times.

[0052] Performance characterization:

[0053] Particle size test method: The particle size test was performed using a Mastersizer 3000 laser particle size analyzer. The particle size was tested, and then the slurry after high pressure dispersion was sealed and stored for 12 and 24 hours, and the particle size was tested to check the slurry stability. The results are shown in Table 1.

[0054] Table 1

[0055] Particle size Dv(90) / nm Serum Let stand for 12 hours Let stand for 24 hours Example 1 389 378 393 Example 2 226 230 232 Example 3 200 205 218 Example 4 545 989 1245 Example 5 540 578 602 Example 6 575 624 756 Comparative Example 1 425 853 1023 Comparative Example 2 445 680 725 Comparative Example 3 467 623 689

[0056] It can be seen from the particle size change data that in implementation cases 1, 2 and 3, as the dispersion pressure increases, the particle size of the catalyst clusters gradually decreases. As time increases, the particle size of the clusters does not change much, indicating that the slurry can be stored stably. From Example 4, it can be seen that as the dispersion pressure exceeds the critical value, the catalyst clusters are over-dispersed, the clusters are more unstable, the cluster particle size increases, and the slurry is unstable. From Examples 5 and 6, it can be seen that the ratio of the first ionomer to the second ionomer I / C has a certain effect on the stability of the slurry. As the ratio of the first ionomer I / C increases, the stability of the slurry deteriorates, indicating that the catalyst clusters are unstable and not conducive to slurry storage. From the comparative case, it can be seen that only one ionomer is used, and the clusters formed by the catalyst particles being coated with perfluorosulfonic acid resin are unstable, which is not conducive to the stability of the slurry clusters, and it is not easy to form a stable slurry.

[0057] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a catalyst slurry, characterized in that: include: Premixing the first ionomer solution and the catalyst, and then adding the first solvent to the system for first mixing to form a first slurry; performing a second mixing of the first slurry, the second ionomer solution and the second solvent to form a second slurry; performing high-pressure nano-dispersion on the second slurry to obtain the catalyst slurry; Wherein, in terms of weight percentage, the first ionomer solution comprises 5-30wt% of perfluorosulfonic acid resin and 70-95wt% of water; the second ionomer solution comprises 5-30wt% of perfluorosulfonic acid resin, 10-70wt% of alcohol solvent and 0-50wt% of water.

2. The method for preparing the catalyst slurry according to claim 1, characterized in that: The catalyst is selected from one or more of a platinum-carbon catalyst, a platinum-cobalt alloy-carbon catalyst or a platinum-cobalt-manganese ternary alloy-carbon catalyst.

3. The method for preparing the catalyst slurry according to claim 2, characterized in that: The I / C value of the catalyst slurry is 0.4 to 1.2; Preferably, the ratio of the I / C value of the first ionomer solution to the I / C value of the second ionomer solution is 0.25 to 3:

1.

4. The method for preparing the catalyst slurry according to claim 1, characterized in that: The ion exchange equivalent value of the first ionomer solution is less than the ion exchange equivalent value of the second ionomer solution; Preferably, the ion exchange equivalent value of the first ionomer solution is ≤810; Preferably, the ion exchange equivalent value of the second ionomer solution is ≤1050.

5. The method for preparing the catalyst slurry according to claim 1, characterized in that: The temperature of the first solvent and the second solvent are independently -5 to 10°C; Preferably, the first solvent and the second solvent are each independently selected from C1-C3 alcohol solvents, and more preferably, the first solvent and the second solvent are each independently selected from one or more of n-propanol, isopropanol, ethanol or methanol.

6. The method for preparing the catalyst slurry according to claim 1, characterized in that: The stirring rate during the premixing process is 50 to 200 rpm, and the stirring time is 5 to 60 min; Preferably, the stirring rate in the first mixing process is 100 to 500 rpm, and the stirring time is 20 to 40 min; Further preferably, the stirring rate in the second mixing process is 50 to 500 rpm, and the stirring time is 30 to 180 min.

7. The method for preparing the catalyst slurry according to claim 1, characterized in that: The dispersion pressure in the high-pressure nano-dispersion process is 80-150 MPa, and the number of nano-dispersion times is 3-8 times.

8. The method for preparing the catalyst slurry according to claim 1, characterized in that: The solid content of the catalyst slurry is 8-14 wt %.

9. A catalyst slurry prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the catalyst slurry according to claim 9 in the preparation process of a proton exchange membrane fuel cell.

Citation Information

Patent Citations

  • Preparation method of catalyst slurry for membrane electrode of fuel cell

    CN106654309A

  • Preparation method of fuel cell membrane electrode slurry

    CN109390593A

Cited By

  • Preparation method and application of catalyst layer of fuel cell membrane electrode

    CN120545383A